Effects of Same-Sex Marriage Legalization for Sexual Minority Men in Taiwan: Findings From a Prospective Study - Yu-Te Huang; Zurong Liang (Frontiers Media S.A., 2022)
Objective: On May 24, 2019, same-sex marriage (SSM) was legalized in Taiwan. Increasing research in western countries has yielded longitudinal evidence about the psychosocial benefits of SSM for sexual minority individuals, but they have rarely included sexual minority-specific measures or considered participants' relationship status. This study aimed to examine the short-term effects associated with the legalization of SSM for gay and bisexual men in Taiwan.Methods: A panel sample of 731 gay and 132 bisexual men participated in baseline (May 2019) and follow-up (October 2020) online surveys to report their depressive symptoms, distal sexual minority stress, internalized homophobia, and outness status.Results: The results demonstrated significant reductions in depressive symptoms and distal sexual minority stress along with increased rates of coming out to friends, family, and parents. These changes were similar for partnered and un-partnered individuals. Fixed-effect regression analysis indicated that the decline in distal sexual minority stress and internalized homophobia contributed to the decline in depressive symptoms.Conclusion: This study preliminarily supports the positive effects of SSM in promoting sexual minority men's mental health and disclosure in Taiwan.